Significant Association of Adam 33 Polymorphism with COPD in Javanese Population of Indonesia - Retno Ariza Soeprihatini Soemarwoto; Jamsari; Yanwirasti; Andika Chandra Putra; Syazili Mustofa; Wawan Abdullah Setiawan; Ifan Aulia Candra (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of World health cases that is commonlyknown, which is triggered by the combination of environmental factors especially cigarette smoking andgenetic factors. The association between A disintegrin and metalloprotease 33 (ADAM33) polymorphismsand COPD has been investigated and reported by other researchers. Objective: The main aim of this study isto identify the association between single nucleotide polymorphisms (SNPs) in ADAM 33 gene with COPDin the Javanese population in Lampung, Indonesia. Methods: A randomized cross-sectional study was usedin this research. PCR-Sequencing method was involved to analyze the polymorphic for three SNPs (T1, T2,and Q-1) of the ADAM33 gene. Statistical analysis data was performed in descriptive and comparative aswell as it was measured by parametric/non-parametric tests. Results: The results showed that the T2 GG,and T1AG genotypes in COPD group were significantly more frequent rather than in control group (p <0.05). In case of allele, it was found that the T1G and T2G was higher in COPD group rather than in thecontrol group (p = 0.440 and 0.131, respectively). Conclusion: The results clearly conclude that there wassignificant association between T1 and T2 polymorphisms of ADAM33 gene and COPD in the Javanesepopulation of Lampung, Indonesia.